On Whose Authority? A Collaborative Self-Study into Service-User Involvement and Simulation-based Learning in Child and Youth Care Education - Ali, Jasmine; Boileau, Kerry; Haskett, Miranda; Kipang, Shani; Marksman-Phillpotts, Denysha; Vachon, Wolfgang (International Journal of Child, Youth and Family Studies)

(untitled) (University of Victoria, 2020)
This study offers a preliminary investigation into a simulation-based, service-user-involved teaching model within a post-secondary child and youth care program. Using the method of collaborative self-study, this research draws on the diverse perspectives of six co-researchers, documenting our experience of this model through the lenses of student, professor, youth trainer, and facilitator. This study uses praxis (the cycle of action and reflection) and dialogic learning (learning through dialogue) to unpack personal and professional questions of expertise, participation, professional development, and anti-oppressive practice.